The Relationship of Remittance with the Level of Welfare of Household Indonesian Overseas Workers in Tulungagung Village - Kofi, Novrianus; Taek, Emanuel Mau; Firmansyah, Billy (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
This research aims to analyze the relationship between remittances and the level of welfare of overseas migrant worker households in Tulungagung Village, Kertasemaya District. This research uses a descriptive analysis method using a quantitative approach, data quality tests such as validation, reliability, normality, r square and correlation tests. The research results show that remittanceshave a relationshipwith the level of welfare of overseas migrant worker householdsTulungagung Village, Kertasemaya District, Indramayu Regency. The results of the correlation analysis of the closeness of the relationship showed that the value of Rxy = 0.581 = 58% means that the closeness of the relationship between remittances and the welfare of overseas migrant worker households is moderate.